The use of current transformers for noise detection due to sparking in insulators strings in high voltage transmission lines - Adami, José Feliciano [UNESP]; Martinez, Manuel Luiz Barreira; Bertoleti, Pedro Henrique Fonseca [UNESP]; Senne, Ithamar (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In a general way, in an electric power utility the current transformers (CT) are used to measurement and protection of transmission lines (TL) 1 The Power Line Carriers systems (PLC) are used for communication between electrical substations and transmission line protection. However, with the increasing use of optical fiber to communication (due mainly to its high data transmission rate and low signal-noise relation) this application loses potentiality. Therefore, other functions must be defined to equipments that are still in using, one of them is detecting faults (short-circuits) and transmission lines insulator strings damages 2. The purpose of this paper is to verify the possibility of using the path to the ground offered by the CTs instead of capacitive couplings / capacitive potential transformers to detect damaged insulators, since the current transformers are always present in all transmission lines (TL's) bays. To this a comparison between this new proposal and the PLC previous proposed system 2 is shown, evaluating the economical and technical points of view. ©2010 IEEE.
Keywords: Capacitive couplings; Current transformer; Data transmission rates; Electric power utilities; Electrical substations; High voltage transmission lines; Insulator string; Noise detection; Potential transformer; Power line carrier; Signal-noise relation; Transmission line; Transmission line protection; Bandpass filters; Data communication systems; Electric instrument transformers; Optical communication; Optical fibers; Power transformers; Surge protection; Transformer protection; Transmission line theory; Electric lines